Acute Kidney Injury Due to Acute Cortical Necrosis Following a Single Wasp Sting. (February 2013) - Kumar, Vivek; Nada, Ritambhra; Kumar, Sravan; Ramachandran, Raja; Rathi, Manish; Kohli, Harbir S.; Sakhuja, Vinay; Jha, Vivekanand
<x xml:space="preserve">Abstract</x> Acute kidney injury (AKI) can develop after multiple wasp or bee stings. The etiology is the acute tubular necrosis secondary to shock, pigment toxicity, interstitial nephritis, or direct nephrotoxicity of venom. We report a 40-year-old female who presented with oliguric AKI after a single wasp sting on her hand. Her history, examination, and investigations did not support any of the established causes of AKI in such settings. She did not improve with supportive management and dialysis, and kidney biopsy showed acute cortical necrosis (ACN). This is the first report of ACN after a single wasp sting.